1994
DOI: 10.1007/bf02473388
|View full text |Cite
|
Sign up to set email alerts
|

The beneficial effects of aminophylline administration on heparin reversal with protamine

Abstract: The aim of this study was to demonstrate the beneficial effects of aminophylline on protamine cardiotoxicity. Thirty-four patients were examined, 17 of whom received aminophylline 3 mg/kg before protamine administration, being the study group, while the other 17, being the control group, did not. All cardiac output and biochemical measurements were evaluated 5 min following protamine administration. The cAMP level was 43.4 +/- 3.51 pmol/ml in the study group and 18.7 +/- 2.98 in the control group (P < 0.0001) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In previous studies, it was shown that aminophylline and prostacyclin protected the heart from protamine cardiotoxicity by elevating the cAMP level. 14,15 The most marked effects of aminophylline were observed during the early reperfusion period in terms of volume-pressure relationship and myocardial metabolism. In group 2 under maximal volume loading conditions, there was better contractile activity, increased oxidative activity, and less lactate release compared with the other groups, indicating reduced injury.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, it was shown that aminophylline and prostacyclin protected the heart from protamine cardiotoxicity by elevating the cAMP level. 14,15 The most marked effects of aminophylline were observed during the early reperfusion period in terms of volume-pressure relationship and myocardial metabolism. In group 2 under maximal volume loading conditions, there was better contractile activity, increased oxidative activity, and less lactate release compared with the other groups, indicating reduced injury.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other agents such as aprotinin and steroids, aminophylline is safe and cost-effective, and has no risk of increasing potential infection, thromoembolism, and allergic reactions. In addition, aminophylline was also used to neutralize the adverse effect of protamine in cardiac operation [23], improved the sinus node dysfunction in heart transplantation [24]. We think that anti-inflammatory effect of aminophylline may also be beneficial for the patients undergoing open heart operation.…”
Section: Commentmentioning
confidence: 97%
“…One of the lesser known benefits of aminophylline is the alleviation of side effects produced by protamine when used for heparin neutralization; the so-called protamine-induced cardiotoxicity. 35 Other reported beneficial effects of aminophylline have been the observed trend toward favorable diuresis in patients following major abdominal surgery, 36 its reversal of high-grade AV block during dipyridamole stress testing, 37 its benefit in cardiopulmonary resuscitation during cardiac arrest with asystole, 38 its improvement of functional renal impairment that occurs in patients with hepatic cirrhosis, 39 and the normalization of profound sinus node dysfunction that occurs in some patients following cardiac transplantation. 40 Other anecdotal reports of possible benefit have been in the alleviation of Cheyne-Stokes respiration, neonatal sleep apnea, bronchodilatory assistance in patients with advanced cystic fibrosis, the reduction of essential neurogenic tremor, and as adjunctive therapy in patients with chronic lymphocytic leukemia.…”
Section: Additional Cardiovascular Considerationsmentioning
confidence: 99%